Kesadaran Hukum Pendaftaran Merek Pada Pelaku Usaha Mikro & Kecil Di Kecamatan Tanah Pinoh Kabupaten Melawi - Riswana, Irma Fitri; Febriany, Tri Atika; Kurniawan, Heru Yudi (Faculty of Law, Universitas Muhammadiyah Pontianak, 2024)
This research aims to analyze the level of legal awareness and the obstacles faced by Micro and Small Enterprises (UMK) in the trademark registration process in Tanah Pinoh District, Melawi Regency. In an increasingly competitive global market, protecting intellectual property, particularly trademarks, is crucial to ensuring product identity and market competitiveness. However, many UMK actors are unaware of the legal importance of trademark registration, resulting in a lack of protection for their business assets. The study employs a juridical-empirical approach, with primary data obtained through interviews with UMK actors and related agencies, and secondary data from literature reviews. The findings reveal that low legal literacy, limited government outreach, and the perception that trademark registration is complicated and costly are major obstacles. Even when free registration programs are available, participation rates remain low.Trademarks serve not only as unique identifiers but also as legal safeguards that ensure business continuity and prevent infringement or duplication. Registration enhances product credibility and consumer trust. Therefore, more effective strategies are needed to raise awareness among UMK actors through sustained legal education, simplified administrative processes, and stronger regional government support. This research aims to inform policymakers in designing fairer and more inclusive intellectual property protection strategies for small-scale businesses.